2021
DOI: 10.7570/jomes20137
|View full text |Cite
|
Sign up to set email alerts
|

Framingham Risk Score Assessment in Subjects with Pre-diabetes and Diabetes: A Cross-Sectional Study in Korea

Abstract: This is a PDF file of an article accepted, but it is not yet the definitive version of record.Background: This study aimed to evaluate cardiovascular risk in subjects with pre-diabetes and diabetes in Korea. Methods:In this pan-Korean, non-interventional, cross-sectional study, data were collected from medical records of 10 hospitals between November 2013 and June 2014. Subjects (aged ≥40 years) with medical records of dysglycemia and documentation of total cholesterol level, high-density lipoprotein cholester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Lipids are considered an essential hazard for the progression of prediabetes into diabetes and combined cardiovascular complications. A non-interventional cross-sectional study conducted in South Korea showed that prediabetes combined with abnormal lipid metabolism (high TG, low HDL-C) was 2.89 times more likely to develop cardiac complications later in life than patients with normal lipid metabolism ( Kwon et al, 2021 ). Therefore, targeted measures should be taken to enhance the management of dyslipidemia in prediabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Lipids are considered an essential hazard for the progression of prediabetes into diabetes and combined cardiovascular complications. A non-interventional cross-sectional study conducted in South Korea showed that prediabetes combined with abnormal lipid metabolism (high TG, low HDL-C) was 2.89 times more likely to develop cardiac complications later in life than patients with normal lipid metabolism ( Kwon et al, 2021 ). Therefore, targeted measures should be taken to enhance the management of dyslipidemia in prediabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous tools are available for assessing cardiovascular risk. The Framingham Heart Study (FHS), one of the well-known cardiovascular riskpredicting models, plays a crucial role in the management of care, evaluation of intervention outcomes, and establishment of risk strati cation [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The TG/HDL ratio has gained interest as a potential indicator of cardiovascular risk, providing a straightforward and e cient method for initial evaluation. Traditional approaches to risk assessment, including the use of the FHS Cardiovascular Risk Score, are widely applied for predicting CVD risk over the long term [7,8,22,23]. However, including the TG/HDL ratio in these models remains underexplored, especially in individuals with T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Various CV risk assessment algorithms have been developed, but their applicability to subjects with diabetes is uncertain [ 10 , 11 ]. The Framingham risk score (FRS) is one of the most effective cardiovascular risk calculators used globally in clinical practice to identify and treat high-risk populations and effectively communicate risk [ 12 , 13 ]. In Thailand, although a Thai CV risk score developed based on a specific career population is available, further external validation is still needed [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%